Cooking and Commensality Along the Bering Food Bridge - Yamin-Pasternak, Sveta; Pasternak, Igor (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2021)
In the decades following the 1988 Nome-Provideniya Friendship Flight that marked the beginning of a “thaw” in US-USSR Cold War politics, the Bering Strait region has been the site of continuous exchanges between the Indigenous communities of Chukotka and Alaska. Ranging from relatively small family reunions to regional multi-community events, these bilateral transcontinental gatherings have facilitated the sharing of Indigenous knowledge, languages, and expressive culture—all reflected in present-day ideas and practices surrounding food. Envisioning the Bering Food Bridge as both a metaphor and a model for exploring culture and cuisine, this article employs a synergistic framework of anthropological and artistic research to offer an ethnographic excursion into the contemporary foodways in the Yupik, Inupiaq, and Chukchi communities in the region of the Bering Strait.